Charge‐Trap Flash‐Memory Oxide Transistors Enabled by Copper–Zirconia Composites. (10th September 2014) - Baeg, Kang‐Jun; Kim, Myung‐Gil; Song, Charles K.; Yu, Xinge; Facchetti, Antonio; Marks, Tobin J.
<x xml:space="preserve">Abstract</x> A solution‐processed electrochemical charge‐trap flash memory element is based on a solid solution of copper and zirconium oxides (Cu‐ZrO2) as a charge‐trapping layer. Because of the facile reduction of Cu2+ to Cu1+, Cu‐ZrO2 thin films are especially effective in memory devices based on thin‐film transistors when the devices are fabricated from combustion‐processed metal–oxide semiconductors (In2O3 and an indium–gallium oxide). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>